DARI JALUR SUTRA KE NUSANTARA: AKULTURASI ARSITEKTUR TIONGHOA ISLAM DI INDONESIA - Chayara Evrillica; Jesselyn Yobella Shalom; Vina Putri Aryani (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study examines the acculturation of Chinese Islamic architecture in Indonesia through cultural interactions that have taken place since the Silk Road era. This acculturation is reflected in the presence of Chinese Islamic–style mosques, such as the Muhammad Cheng Hoo Mosque in Surabaya, the Lautze Mosque in Jakarta, and the Siti Djirzanah Mosque in Yogyakarta, which integrate elements of traditional Chinese temple architecture with Islamic principles. This study is directed toward analyzing the process of development of Chinese Islamic architectural acculturation as well as examining the forms of cultural integration and social meanings reflected in mosque buildings. This study employs a qualitative approach using a library research method to obtain an in-depth understanding of the acculturation of Chinese Islamic architecture in Indonesia. This approach was selected because the research focuses on the interpretation of meaning, cultural context, and architectural symbols that cannot be reduced to numerical data. The data were analyzed using a descriptive qualitative method by synthesizing findings from various relevant and credible scholarly sources. The primary contribution of this study lies in the formulation of the characteristics of Chinese Islamic–style mosque architecture as a form of cultural acculturation and as a representation of social meanings within the context of Islamic diversity in Indonesia.